2021
DOI: 10.4244/eij-d-21-00348
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, prospective, randomised controlled trial to assess the safety and effectiveness of cooling as an adjunctive therapy to percutaneous intervention in patients with acute myocardial infarction: the COOL AMI EU Pivotal Trial

Abstract: Background: Despite primary PCI (PPCI), STEMI can still result in large infarct size (IS).New technology with rapid intravascular cooling showed positive signal for reduction in IS in anterior STEMI.Aims: We investigated the effectiveness and safety of rapid systemic intravascular hypothermia as an adjunct to primary PCI (PPCI) in conscious patients with anterior STelevation myocardial infarction (STEMI) without cardiac arrest.Methods: Hypothermia was induced using ZOLL ® Proteus™ Intravascular Cooling System.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…However, a recently published report concluded that out-of-hospital induced cooling, as an adjunct to primary percutaneous coronary intervention did not improve myocardial salvage as assessed with CMR in patients with STEMI [ 19 ]. Additionally, in the Cool-AMI study, a reduction of body core temperature to 33.3 °C before primary PCI in patients with anterior STEMI was associated with increased risk for adverse events [ 20 ]. Concomitant reduced fall in levels of CK-MB in the 48 h treatment arm compared with the 24-h arm in a sub-study of the TTH 48 trial further support the potential deleterious effects on the myocardium of TTM for comatose survivors of OHCA in patients with AMI [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recently published report concluded that out-of-hospital induced cooling, as an adjunct to primary percutaneous coronary intervention did not improve myocardial salvage as assessed with CMR in patients with STEMI [ 19 ]. Additionally, in the Cool-AMI study, a reduction of body core temperature to 33.3 °C before primary PCI in patients with anterior STEMI was associated with increased risk for adverse events [ 20 ]. Concomitant reduced fall in levels of CK-MB in the 48 h treatment arm compared with the 24-h arm in a sub-study of the TTH 48 trial further support the potential deleterious effects on the myocardium of TTM for comatose survivors of OHCA in patients with AMI [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple randomized controlled trials have studied hypothermia for cardioprotection, and all were negative for the primary endpoint, either IS or IS/MaR [26][27][28][29][30][31][32]. A study-level meta-analysis of randomized trials investigating systemic hypothermia for cardioprotection in STEMI (Figure 1) did not show a decrease in IS compared to standard PCI (standardized mean difference of IS −0.17, 95% confidence interval −0.52 to 0.19).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…It is obvious that cooling methods that intend to cool the entire body are by definition time-consuming. Even the strongest cooling devices cause a delay in treatment [32]. This delay (with longer ischemic time) is at the expense of the benefit achieved by hypothermia.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, although not statistically significant (8.6% vs. 1.9%; p = 0.12), there was an excess of major adverse events-including atrial fibrillation, ventricular tachycardia/fibrillation, and stent thrombosis. Actually, the study was stopped prematurely due to a 44-min increase in total ischemic delay in the hypothermia group [70].…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%